Validity and test-retest reliability of a smartphone app for measuring rising time, velocity, power, and inter-limb asymmetry during single-leg sit-to-stand test in female-trained athletes - Makaraci, Y.; Nas, K.; Gündüz, K.; Uysal, A.; Orange, S. T.; Ruiz-Cárdenas, J. D. (Measurement in Physical Education and Exercise Science, 2024)
The aim was to determine the validity and test - retest reliability of the Sit to Stand App variables (rising time, vertical velocity, and power) for measuring single-leg sit-to-stand (STS) test compared to those derived from ground reaction force data. Twenty-seven female athletes performed the single-leg STS test over three consecutive sessions simultaneously recorded with a force plate and the smartphone app. Validity was assessed with Pearson`s correlation coefficient, intra-class correlation coefficient (ICC), and percentage error. Reliability was assessed with the ICC. Almost perfect correlations (r = 0.95) and excellent agreement (ICC = 0.96-0.97) between the app and force plate measures with low percentage errors (=7.3%) were found. The app showed good-to-excellent reliability (ICC = 0.88-0.92) with no differences in inter-limb asymmetry over three sessions. The app was highly valid and reliable for measuring single-leg STS performance. Practitioners can use this app to assess lower-limb performance in female athletes.